Transcriptome-wide identification of Rauvolfia serpentina microRNAs and prediction of their potential targets. (April 2016) - Prakash, Pravin; Rajakani, Raja; Gupta, Vikrant
Graphical abstract: Highlights: Fifteen conserved microRNAs were identified from Rauvolfia serpentina . Uracil was preferred initial base (86.67%) of identified mature miRNA sequences. Phylogenetic analysis revealed pre-miRNAs evolutionary relationship across species. Thirty six potential targets of identified miRNAs were predicted in R. serpentina . Predicted targets were associated with regulation of diverse biological processes. Abstract: MicroRNAs (miRNAs) are small non-coding RNAs of ∼19–24 nucleotides (nt) in length and considered as potent regulators of gene expression at transcriptional and post-transcriptional levels. Here we report the identification and characterization of 15 conserved miRNAs belonging to 13 families from Rauvolfia serpentina through in silico analysis of available nucleotide dataset. The identified mature R. serpentina miRNAs (rse-miRNAs) ranged between 20 and 22 nt in length, and the average minimal folding free energy index (MFEI) value of rse-miRNA precursor sequences was found to be –0.815 kcal/mol. Using the identified rse-miRNAs as query, their potential targets were predicted in R. serpentina and other plant species. Gene Ontology (GO) annotation showed that predicted targets of rse - miRNAs include transcription factors as well as genes involved in diverse biological processes such as primary and secondary metabolism, stress response, disease resistance, growth, and development. Few rse-miRNAs were predicted to target genes of pharmaceutically important secondary metabolic pathways such as alkaloids and anthocyanin biosynthesis. Phylogenetic analysis showed the evolutionary relationship of rse-miRNAs and their precursor sequences to homologous pre-miRNA sequences from other plant species. The findings under present study besides giving first hand information about R. serpentina miRNAs and their targets, also contributes towards the better understanding of miRNA-mediated gene regulatory processes in plants.